Speaking materialities: dialogues between artistic archival practices and conservation-restoration (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This work reflects on the memory embedded in the materiality of the image by establishing a dialogue between conservation-restoration and contemporary artistic practices that are based on the use of photographic archival images. Both disciplines create a scenario that allows us to understand the historiographical turn as a paradigm shift in the role of the artist who, adopting the modus operandi of the historian and the curator, intervenes in the photographic archive using strategies that border on the deontological code of conservation-restoration. The intersection between archival artistic practices and conservation reveals the presence of a common criterion that has been forged and developed in parallel: the preservation of the additions of time and history in the materiality of the photographic image, which leads to the recognition of its discursive and narrative capacities. This convergence of perspectives not only emphasizes the preventive conservation of photographic works but also creates a space for dialogue with contemporary artists who construct counter-hegemonic narratives by recovering traditionally denigrated layers of the photographic image, such as the traces and indexical marks that have altered its support. and, consequently, its final aesthetic.
Keywords: Conservation-restoration; history; memory; archive; contemporary art; photograph